2018
DOI: 10.1371/journal.pone.0204498
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia in neonates born to mothers with preeclampsia: Impact of small for gestational age

Abstract: Background and objectivesSmall for gestational age and preeclampsia have both been described as risk factors for bronchopulmonary dysplasia in preterm neonates, but their respective role in the occurrence of bronchopulmonary dysplasia is debated. We evaluated the relation between small for gestational age and bronchopulmonary dysplasia in neonates born to mothers with preeclampsia. We hypothesized that low birth weight is still associated with bronchopulmonary dysplasia in this homogeneous population.MethodsRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
4
9
0
Order By: Relevance
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%) 14–17 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%) 14–17 …”
Section: Discussionsupporting
confidence: 80%
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%). [14][15][16][17] Regarding postnatal history, almost half of our patients received invasive ventilation (51.4%), with a median duration of 2 days. This highlights the need to avoid this type of ventilatory support as much as possible, favoring strategies such as CPAP and/or nasal ventilation from the delivery room.…”
Section: Discussionmentioning
confidence: 98%
“…The history of the OD preterm cohort in this study is similar to that found in the literature, with predominance of male patients and a history of maternal infection in more than 50% of the cases, followed by toxemia (21%) and premature rupture of membranes (6.7%) [14][15][16][17] .…”
Section: Discussionsupporting
confidence: 83%
“…BPD is a respiratory condition occurring in preterm neonates and can lead to chronic respiratory problems driven by several prenatal and/or postnatal factors [20]. The known risk factors associated with BPD development in preterm neonates include small gestational age, preeclampsia, chorioamnionitis and in ltration of the chorioamnion by neutrophils [21,22]. The most likely underlying pathogenesis is the constant in ammation in lung, and thus corticosteroid, which has a strong anti-in ammatory effect, has been employed in the treatment of BPD [23].…”
Section: Discussionmentioning
confidence: 99%